IDENTIFIKASI PERMASALAHAN PENGELOLAAN MUTU TEH DO UNIT USAHA PERKEBUNAN MALABAR PT. NUSANTARA VIII JAWA BARAT - MOHAMAD MAULANA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
Quality has become an important factor for producers facing to global competitionenvironment. This global condition pushed The Malabar Estate as a part of the biggest teaproducers in Indonesia, Perkebunan Nusantara VIII Co., to manage the quality of tea inorder to satisfy consumers need. When Malabar Estate is managing quality of product,there are some problems facing them. The problems could be come from inside or outsidecompany environment. The objective of this paper is to find out problems that could behappened in managing quality of product, put them into a hierarchy and analyze theproblems with Analytical Hierarchy Process Method resulting a priority of problems andcauses of the problems as an input for Perkebunan Nusantara VIII Co., especially forMalabar Estate to fix the problems. Teh result of analyze using Analytical HierarchyProcess (AHP) show that the main problems of managing product quality in MalabarEstate are decreasing quality of product, increasing cost of production and decreasingquantity of production. Generally, the problems causes by managing production process,qualification of employment, environment factor, infrastructure and increasing cost of fueland utilities. The problems causes, in general, intend to controllable causes of problems.That means, the company should take some actions to manage and fix the problemsimmediately.